Developing a Model for Effective Community Organizing Training - Hagins, Noel; Martinez, Christine; McManus, Inga; West, Lola; Chen, Nien-Tsu (CBR@CSUCI: An annual volume of community-based research, 2019)
This study is based on research conducted to evaluate the effectiveness of a three-day community organizing training workshop involving 38 organizers based in Ventura and Santa Barbara counties. The training was co-sponsored by the McCune Foundation, Fund for Santa Barbara, Kaiser Permanente Foundation and Weingart Foundation. Data were collected through baseline surveys conducted with training participants and the Executive Directors of their organizations, as well as field observations by researchers from California State University Channel Islands during the training in April 2017. Descriptive statistics and t-tests were used to analyze survey results, and thematic analysis was performed on the field observation data. The analyses led to a list of recommendations for foundations interested in hosting similar events in Ventura and Santa Barbara counties and beyond in the future.